2011
DOI: 10.1371/journal.pone.0026169
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discovery for Duchenne Muscular Dystrophy via Utrophin Promoter Activation Screening

Abstract: BackgroundDuchenne muscular dystrophy (DMD) is a devastating muscle wasting disease caused by mutations in dystrophin, a muscle cytoskeletal protein. Utrophin is a homologue of dystrophin that can functionally compensate for its absence when expressed at increased levels in the myofibre, as shown by studies in dystrophin-deficient mice. Utrophin upregulation is therefore a promising therapeutic approach for DMD. The use of a small, drug-like molecule to achieve utrophin upregulation offers obvious advantages i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 59 publications
3
64
0
3
Order By: Relevance
“…Mice treated at the higher dose showed little to no improvements in the dystrophic pathology. A similar trend in dose response was observed earlier during a drug-screen for natural compounds that activate the utrophin A promoter (46). With the use of a luciferase reporter promoter assay in cultured myogenic C 2 C 12 cells, it was discovered that RSV could activate the utrophin A promoter, with the maximum fold change in luciferase activity observed at a relatively low dose of 6.25 M. These dose-response effects noted in earlier studies mirror much of what we observed in our investigation.…”
Section: MDXsupporting
confidence: 82%
See 2 more Smart Citations
“…Mice treated at the higher dose showed little to no improvements in the dystrophic pathology. A similar trend in dose response was observed earlier during a drug-screen for natural compounds that activate the utrophin A promoter (46). With the use of a luciferase reporter promoter assay in cultured myogenic C 2 C 12 cells, it was discovered that RSV could activate the utrophin A promoter, with the maximum fold change in luciferase activity observed at a relatively low dose of 6.25 M. These dose-response effects noted in earlier studies mirror much of what we observed in our investigation.…”
Section: MDXsupporting
confidence: 82%
“…Following the 6-wk treatment period, mice were euthanized by CO 2 asphyxiation and cervical dislocation and the tibialis anterior (TA), extensor digitorum longus (EDL), soleus (SOL), and gastrocnemius (GAST) muscles were harvested and immediately frozen in liquid nitrogen or in melting isopentane cooled with liquid nitrogen for histological and immunofluorescence analyses. For the second RSV protocol, treated mdx mice were given a standard control diet, supplemented with RSV (ϳ 500 mg·kg Ϫ1 ·day Ϫ1 ) based on earlier work (29,46), and the duration was extended to 12 wk. This was considered a high dose and a long duration (HDLD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are similar to those found in other studies that have been used in preclinical and clinical trials. For example, the nonsteroidal antiinflammatory drug nabumetone upregulates utrophin protein expression 1.2‐fold in C2C12 cells 26. SMTC1100, a drug tested in phase I clinical trials, upregulated utrophin twofold in human DMD cells and showed an ∼75% increase in expression in the diaphragm of mdx mice 27…”
Section: Discussionmentioning
confidence: 99%
“…29,30 However, recent studies show that regulation of utrophin translation and mRNA stability via UTR-mediated mechanisms is of great importance in the control of utrophin protein levels. Indeed, the repressive posttranscriptional regulation of utrophin may be part of the reason that utrophin upregulating therapies have not yet reached the clinic.…”
Section: Discussionmentioning
confidence: 99%